International NGOs and Social Solidarity Economy in Developing Countries: A Comparative Analysis - Asaad, Ali Hasan (Digital Repository of Theses - SSBM Geneva, 2025)
This study examines how international non-governmental organizations (INGOs) contribute to promoting sustainable development in developing countries, with a particular focus on educational initiatives and bottom-of-the-pyramid (BOP) marketplace interventions. Employing a mixed-methods design, the investigation integrates panel-data econometric estimations over low- and lower-middle-income countries (LLMICs) with in-depth qualitative studies in five selected countries—Syria, the Democratic Republic of the Congo (DRC), Sudan, Bangladesh, and Ukraine. Quantitative findings indicate tentative positive associations between INGO education expenditures and development indicators, such as the Human Development Index (HDI) and new business registrations (NBR). Nonetheless, persistent econometric problems—autocorrelation, cross-sectional dependence, and low model fit—limit the potency of causal interpretations. Complementary qualitative data, collected through questionnaires and coded according to thematic coding, suggests that INGO project prioritization is driven primarily by organizational mandates, community needs, donor requirements, and partnerships—particularly with local governments. However, systemic vulnerability, constrained resources, and contextual constraints usually undermine the sustainability and scalability of their activities. Overall, this study shows that although INGO expenditure on education may be associated with small but substantial gains in HDI, causal relationships remain in doubt and the effect on NBR is unknown due to model instability and macroeconomic policy forces. Such findings speak to the strong context dependency of INGO contributions and to the mediating effects of institutional and structural factors. The study advises subsequent studies to employ advanced causal inference techniques, longitudinal case studies, and participatory research to better elaborate the mechanisms through which INGOs influence development outcomes. Policy contributions emphasize adaptive, data-informed, and community-led approaches to maximize the impact and equity of INGO interventions in low-income and conflict settings.